2020
DOI: 10.3390/ijms21238886
|View full text |Cite
|
Sign up to set email alerts
|

Male-Dependent Promotion of Colitis in 129 Rag2−/− Mice Co-Infected with Helicobacter pylori and Helicobacter hepaticus

Abstract: The prevalence of gastric Helicobacter pylori (Hp) infection is ~50% of the world population. However, how Hp infection influences inflammatory bowel disease in humans is not fully defined. In this study, we examined whether co-infection with Hp influenced Helicobacter hepaticus (Hh)–induced intestinal pathology in Rag2−/− mice. Rag2−/− mice of both sexes were infected with Hh, of which a subgroup was followed by infection with Hp two weeks later. Co-infected males, but not females, had significantly higher to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
3
1
0
Order By: Relevance
“…The increase of Helicobacter and Desulfovibrio has been related to the colitis, and a member of Desulfovibrio could produce endotoxins and toxic sulfur, thereafter inducing inflammation. 59,60 As expected, the results from the integrative analysis demonstrate strong connections between beneficial effects of SeBSP on alleviating BaP-impaired metabolic enzymes, pyroptosis indexes, oxidative and inflammatory factors, and those heath-relevant bacterial taxa. In addition, BaP remarkably increased Akkermansia, which was then reduced by SeBSP.…”
Section: ■ Discussionsupporting
confidence: 67%
“…The increase of Helicobacter and Desulfovibrio has been related to the colitis, and a member of Desulfovibrio could produce endotoxins and toxic sulfur, thereafter inducing inflammation. 59,60 As expected, the results from the integrative analysis demonstrate strong connections between beneficial effects of SeBSP on alleviating BaP-impaired metabolic enzymes, pyroptosis indexes, oxidative and inflammatory factors, and those heath-relevant bacterial taxa. In addition, BaP remarkably increased Akkermansia, which was then reduced by SeBSP.…”
Section: ■ Discussionsupporting
confidence: 67%
“…Similar sexual dimorphism was described in the less used IBD model 129 Rag2 −/− mice [24]. In this scenario, however, the concomitant infection of Helicobacter pylori enhanced the colonic inflammatory response in males, resulting in more severe colitis and dysplasia compared with females [24]. We must remark that the fecal lipocalin-2 levels (Figure 2A), used as a non-invasive inflammatory marker, did not show significant differences between males and females.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, authors reported more severe intestinal inflammation in female mice compared to males, but only by histological injury score and colonic interferon-gamma (IFNγ) secretion. Similar sexual dimorphism was described in the less used IBD model 129 Rag2 −/− mice [ 24 ]. In this scenario, however, the concomitant infection of Helicobacter pylori enhanced the colonic inflammatory response in males, resulting in more severe colitis and dysplasia compared with females [ 24 ].…”
Section: Discussionsupporting
confidence: 67%
“…Secretion of cytokines such as IFN-γ by group 1 ILCs and NCR-ILC3s could contribute to the clearance of intracellular bacteria via promoting activation and phagocytosis by macrophages and dendritic cells [ 16 ]. Meanwhile, the IL-22 production by group 3 ILCs could further induce the production of multiple anti-microbial peptides, such as defensins and cathelicidins from epithelial cells [ 25 , 64 ], as well as RegIIIγ from both epithelial cells and ILC3s [ 65 , 66 , 67 ]. In addition, ILCs are also proposed to be directly involved in regulating gut epithelial integrity [ 16 ].…”
Section: Crosstalk Between Ilcs and Gastric Microbiota And Its Impact...mentioning
confidence: 99%